Identification of Intestinal NaCl Absorptive-Anion Secretory Cells: Potential Functional Significance - Donowitz, Mark; Sarker, Rafiquel; Lin, Ruxian; McNamara, George; Tse, Chung Ming; Singh, Varsha (Frontiers in Physiology, 2022)
Previously, it was believed that there were separate cells involved in intestinal Cl secretion confined to the crypt and Na absorption cells confined to the villus. This view was questioned because the crypt cells differentiate into the villus cells over a few days and the complete switch of the transport processes present in the two cell types represented a large undertaking. Using normal human enteroids, we discovered there was a large population of epithelial cells that contained the transport proteins involved in neutral NaCl absorption and anion secretion. This population makes up the lower villus and upper crypt of the small intestine and surface and upper crypt of the proximal colon. In this partially differentiated cell population, NHE3, DRA and CFTR not only function, but physically interact with each other and affects each other's function. This large cell population contributes to water and electrolyte transport in normal digestive physiology and in pathophysiologic conditions that includes multiple types of diarrheal diseases.